Evil Egyptian Scripts : Abnormal Hieratic, Demotic and Hieratic Texts and Studies in Honour of Koenraad Donker van Heel - Martin, Cary (Papyrologica Lugduno-Batava, 2026)
Evil Egyptian Scripts comprises twenty-nine articles by colleagues and friends in honour of Koenraad Donker van Heel, University Lecturer in demotic papyrology at the Leiden Papyrological Institute. Donker van Heel's research interests embrace the study of demotic and hieratic texts and the legal and social history and economy of ancient Egypt, but he is especially renowned as a specialist in abnormal hieratic, widely regarded as the most difficult of all Egyptian scripts. His numerous textual editions and discussions of problematic readings have been enormously influential and contributed to an ever-increasing recognition of the importance of abnormal hieratic for the study of Egypt in the Third Intermediate and Late Periods. The articles in Evil Egyptian Scripts include editions of abnormal hieratic, demotic and hieratic texts, reading problems, discussions of legal, religious and socio-economic issues and onomastic studies. The timespan of the contributions ranges from New Kingdom Deir el-Medina, through the Third Intermediate and Late Periods and into Graeco-Roman Egypt. The volume is profusely illustrated with many previously unpublished images and supplied with detailed indices.